Origin and evolution of the legitimacy management in higher education - Cruz-Suárez, Ana; Marino, Domenico; Prado-Roman, Camilo (Journal of Management and Business Education, 2020)
What is being researched and which is the sources of knowledge? Those are questions that researchers ask in the construction of new scientific advances. Research on legitimacy and higher education has grown in recent years. This make difficult to get a current view of the situation in which this field of research is. The purpose of this research is to identify and visualize the current state of research in the field of legitimacy and higher education. Through a bibliometric methodology based on co-citations, the current intellectual structure of this research field is analyzed. Furthermore, the main research areas, the main contributors and the means of dissemination of this knowledge are identified. This work contributes to the development of the field of legitimacy and higher education by providing an integral vision of the situation of this domain, a starting point and an adequate theoretical basis for researchers to build new advances.